This question is continuing from the previous question here:

Power Series representation of $\frac{1+x}{(1-x)^2}$

I am trying to calculate the power series representation of the equation:

$$ \begin{align} f(x) = \frac{1+x}{(1-x)^2} \end{align} $$

My workout is as follow:

$$ \begin{align} \frac{1+x}{(1-x)^2} = \frac{1}{(1-x)^2} + \frac{x}{(1-x)^2} \end{align} $$

For $\frac{1}{(1-x)^2}$: \begin{align} \frac{1}{(1-x)^2} &= \frac{d}{dx} \frac{1}{1-x}\\ &= \frac{d}{dx} \sum_{n=0}^{\infty} x^n \\ &= \sum_{n=1}^{\infty} nx^{n-1} \\ &= \sum_{n=0}^{\infty} (n+1)x^n \end{align}

For$\frac{x}{(1-x)^2}$: $$ \begin{align} x \frac{1}{(1-x)^2} &= x \sum_{n=0}^{\infty}(n+1)x^n \\ &= \sum_{n=0}^{\infty} (n+1) x^{n+1} \end{align} $$

Therefore, $$ \begin{align}\frac{1+x}{(1-x)^2} = \sum_{n=0}^{\infty} (n+1)x^n+\sum_{n=0}^{\infty} (n+1) x^{n+1} = \sum_{n=0}^{\infty}(n+1)(x^n + x^{n+1}),\end{align} $$ where range of convergence is $x\in[-1,1)$. When $x=-1$, $(x^n + x^{n+1})$ becomes $0$, and $(\infty)(0) = 0$.

However, the model answer is $\sum_{n=0}^{\infty} (2n+1) x^n$, where range of convergence is $x\in (-1,1)$.

I do not understand what is wrong with my calculation. Any advice will be appreciated!

  • 1
    $\begingroup$ What is incomplete in your approach is that $\sum\limits_{n=0}^{\infty}(n+1)(x^n + x^{n+1})$ is not the canonical form of a power series, which should rather be expressed as $\sum\limits_{n=0}^{\infty}a_nx^n$ for some suitable sequence $(a_n)$. $\endgroup$
    – Did
    Feb 14, 2016 at 10:48
  • $\begingroup$ What should I do? In addition, term by term, the terms in my solution and the model answer are different. $\endgroup$
    – Joseph
    Feb 14, 2016 at 10:50
  • $\begingroup$ Was my solution wrong? The first term in my solution is $1+x$ but the first term in the model answer is $1$. $\endgroup$
    – Joseph
    Feb 14, 2016 at 10:52
  • 1
    $\begingroup$ Why does it seems that $f(x)\neq \sum_{n=0}^{\infty}(n+1)(x^n + x^{n+1})$? You conclude this by looking at the first term of the sum. In your answer that is $1+x$, in the given solution it is $1$, so it can't tbe the case that $f(x) = \sum_{n=0}^{\infty}(n+1)(x^n + x^{n+1})$, right? Wrong, because it can very well be that the "sums" (i.e. the series) are equal even though the first term isn't. The same way $1+2+3=2+1+3$ even though $1\neq 2$. $\endgroup$
    – Git Gud
    Feb 14, 2016 at 11:06
  • 1
    $\begingroup$ for $x=-1$, what you are doing is addition of two oscillating series which turns out to be zero. It is exact same thing like addition of $-1+1-1+1-1+1-1+...$ and $1-1+1-1+1-1+1-...$ becomes zero. $\endgroup$ Feb 14, 2016 at 11:07

2 Answers 2


You did not end up with power series yet: \begin{align*} \sum_{n=0}^{\infty} (n+1)x^n+\sum_{n=0}^{\infty} (n+1) x^{n+1} &=\sum_{n=0}^{\infty} (n+1)x^n+\sum_{n=1}^{\infty} n x^{n}\\ &=\sum_{n=1}^{\infty} (2n+1) x^{n} + 1\\ &=\sum_{n=0}^{\infty} (2n+1) x^{n}\\ \end{align*}

From here you can derive correct radius of convergence.


Hint: In order to find the power series expansion around $x=0$ you could also use the binomial series representation

\begin{align*} (1+x)^\alpha=\sum_{n=0}^{\infty}\binom{\alpha}{n}x^n\qquad\qquad \alpha\in\mathbb{C}, |x|<1 \end{align*}

We obtain \begin{align*} \frac{1+x}{(1-x)^2}&=(1+x)\sum_{n=0}^{\infty}\binom{-2}{n}(-x)^n\tag{1}\\ &=(1+x)\sum_{n=0}^{\infty}\binom{n+1}{n}x^n\\ &=(1+x)\sum_{n=0}^{\infty}(n+1)x^n\\ &=\sum_{n=0}^{\infty}(n+1)x^n+\sum_{n=0}^{\infty}(n+1)x^{n+1}\tag{2}\\ &=\sum_{n=0}^{\infty}(n+1)x^n+\sum_{n=1}^{\infty}nx^{n}\\ &=\sum_{n=0}^{\infty}(2n+1)x^n \end{align*}


  • In (1) we use the identity $\binom{-n}{k}=\binom{n+k-1}{k}(-1)^k$

  • In (2) we shift the index of the right sum by one


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.